Jejak Khulafaur Rasyidin 2 Umar bin Khatab / Sami bin Abdullah Al-Maghlouth; penerjemah, Muflih Kamil; editor, Abdulkarim Khiaratullah dan Fakhron Fillah - MAGHLOUTH, Sami bin Abdullah; MUFLIH Kamil; ABDULKARIM Khiaratullah; FAKHRON Fillah (Almahira, 2014)
xx, 428 hlm. : Ilus. ; 29 cm.